Characteristics of soybean yield influenced by the application of herbicides oxyfluorfen and pendimethalin. Issue 1 (February 2021) - Hasanuddin,; Hafsah, S; Hayati, E; Nurahmi, E; Halimursyadah,; Saputri, U N; Manfarizah,; Aryani, D S
Abstract: Type and dose of herbicides are important factors affecting weed control efficacy on soybean crop. This research was conducted to discover the effective doses of oxyfluorfen and pendimethalin to control weeds, starting from May to August 2019 in Meunasah Manyang Village, Krueng Barona Jaya District, Aceh Besar Regency, Aceh, using Randomized Completely Block Design (RCBD) Factorial. The first factor was type of herbicide: oxyfluorfen and pendimethalin, and the second factor was doses of herbicide: 0, 0.5, 1, 1.5 and 2 kg ai ha -1 . The results showed that type of herbicide affected the weed dry weight, number of seeds per plant and number of pods per plant. Oxyfluorfen reduced weed dry weight but it increased the number of seeds per plant and number of pods per plant. The application of different doses also affected weed dry weight, number of pods per plant and weight of 100 seeds, where dose 1.5 kg ai ha -1 lowered weed dry weight but it also improved the weight of 100 seeds. There was an interaction between type and dose of herbicide on the number of pods per plant. It showed that the application of 1.5 kg ai ha -1 oxyfluorfen increased the number of pods per plant.